On the Intensity of Exploitation of Berried Females of Macrobrachium rosenbergii (de Man) in the Vembanad Lake - M., Harikrishnan; B., Madhusoodana Kurup (Fishery Technology, 2025)
The annual exploited stock of Macrobrachium rosenbergii during 1994-95 from Vembanad lake is computed at 112.35 tons of which 66.22 tons was constituted by the female population. Contribution of berried and spent females were in the order of 23.43 tons and 5.02 tons respectively. Highest exploitation of berried (13.24 tons) and spent (3.39 tons) females were noticed in October while zone 11 accounted for maximum landings of berried prawns (3.6 tons). More than 50% of the berried females were found to be exploited from upstream part of the lake during September and October. In zone 4, 49.59% of the total spawner was comprised of spent females in the month of October. Among the various type of fishing gears and methods, "Pongu Veechal" accounted for exploitation of 75 and 79% of berried and spent females respectively. Temporal and spatial variations in the intensity of exploitation of ovigerous females and spent females are given. Intensity of recruitment over fishing being exercised on the stock of M. rosenbergii of Vembanad lake is brought out and the methods by which conservationÂ measures can easily be imposed forÂ replenishment of stock is also highlighted.